Peripheral fundus findings in X-linked retinoschisis. Issue 11 (27th March 2017) - Fahim, Abigail T; Ali, Naser; Blachley, Taylor; Michaelides, Michel
Abstract : Background/aims: Vitreous haemorrhage (VH) and retinal detachment (RD) cause a precipitous decline in vision in a subset of patients with X-linked retinoschisis (XLRS), an otherwise a slowly progressive condition. This study aims to report the frequency of macular and peripheral retinal findings in a large cohort of patients with XLRS and to determine whether peripheral retinal findings are associated with VH and RD. Methods: A retrospective observational case series was performed in 65 patients with XLRS with a pathogenic variant in retinoschisin 1. Chart review included examination notes, fundus photographs and optical coherence tomography (OCT). Fisher exact tests and univariable logistic regression analysis were used to determine the association between peripheral retinal findings (including retinoschisis, metallic sheen, vascular sheathing, pigmentary changes, white spiculations and vitreous veils) and complications (including VH and RD). Results: Seven eyes (8%) showed normal macular structure on OCT. Peripheral retinoschisis was significantly associated with both VH and RD. Out of 10 eyes with complications, 9 (90%) had peripheral retinoschisis, compared with 33 out of 116 eyes (28%) without complications (p=0.0014). In addition, each additional peripheral finding increased the odds of RD by a factor of 4.06 (95% CI 1.58 to 10.39, p=0.028). There were no complications in the 28 eyes with a normal periphery (p=0.84) or in the 35 eyes with metallic sheen (p=0.42). Conclusion: The data suggest that patients with peripheral retinoschisis are at increased risk for VH and RD. Furthermore, patients with additional peripheral retinal findings together with peripheral schisis may carry additional risk for RD.